Plugging the explicit σ-holes in molecular docking - Kolář, Michal; Hobza, Pavel; Bronowska, Agnieszka K. (Chemical communications, 2013)
A novel approach in molecular docking was successfully used to reproduce protein-ligand experimental geometries. When dealing with halogenated compounds the correct description of halogen bonds between the ligand and the protein is shown to be essential. Applying a simple molecular mechanistic model for halogen bonds improved the protein-ligand geometries as well as halogen bond features, which makes it a promising tool for future computer-aided drug development.
First published: 14 Dec 2012
Gesehen am 25.03.2021